1919
DOI: 10.1002/hlca.19190020164
|View full text |Cite
|
Sign up to set email alerts
|

Über neue organische Phosphorverbindungen III. Phosphinmethylenderivate und Phosphinimine

Abstract: Benzoyldiazoessigester reagiert ebenfalls rnit beiclen Phosphineri. Die erhaltenen Azine werden spater beschrieben.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
539
0
15

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,467 publications
(557 citation statements)
references
References 0 publications
3
539
0
15
Order By: Relevance
“…[14] In the presence of water this intermediate is hydrolyzed to produce a primary amine 3 and triphenylphosphine oxide (TPPO, 4; Scheme 2).…”
Section: Staudinger Reactionmentioning
confidence: 99%
“…[14] In the presence of water this intermediate is hydrolyzed to produce a primary amine 3 and triphenylphosphine oxide (TPPO, 4; Scheme 2).…”
Section: Staudinger Reactionmentioning
confidence: 99%
“…Generally, problems arising from heterogenic phase hydrogenation can be overcome by reducing the azido group of a pentofuranuronic building block with tertiary phosphines under well-established conditions of the Staudinger reaction (Staudinger and Meyer 1919;Staudinger and Hauser 1921;Leffler and Temple 1967;Gololobov et al 1981;Gololobov 1992;Simone et al 2005;Brase et al 2005;Van Rompaey et al 2005;Temelkoff et al 2006): a method introduced for azidosugars as early as 1964 (Messmer et al 1964). The applicability of the Staudinger reaction in peptide chemistry was confirmed in the early 2000s (Saxon et al 2000;Nilsson et al 2000), and its applicability to solid phase synthesis was shown in the same year (Malkinson et al 2000;Lundquist and Pelletier 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The azido-alcohols 7 and 8 were used in the synthesis of the azido-ethers 9-14 by phase-transfer catalyzed alkylations, which, except for 12, were reduced under hydrogenation conditions in presence of Pd/C to afford the corresponding diamine derivative 15-20 in 74-95% yield. Chemoselective reduction of compound 12 was achieved following the method described by Staudinger, Meyer (1919), using triphenylphosphine. The platinum complexes 1-6 were synthesized by reaction of equimolar amount of the appropriate diamine with K 2 PtCl 4 , in 12-55% (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%